Fundamental Modes of Swimming Correspond to Fundamental Modes of Shape: Engineering I‐, U‐, and S‐Shaped Swimmers - Priyanka Sharan (Wiley, 2021)
Hydrogels have received increased attention due to their biocompatible material properties, adjustable porosity, ease of functionalization, tuneable shape, and Young's moduli. Initial work has recognized the potential that conferring out‐of‐equilibrium properties to these on the microscale holds and envisions a broad range of biomedical applications. Herein, a simple strategy to integrate multiple swimming modes into catalase‐propelled hydrogel bodies, produced via stop‐flow lithography (SFL), is presented and the different dynamics that result from bubble expulsion are studied. It is found that for “Saturn” filaments, with active poles and an inert midpiece, the fundamental swimming modes correspond to the first three fundamental shape modes that can be obtained by buckling elastic filaments, namely, I, U, and S‐shapes.